A lead-tin mixed perovskite solar cell based on buried interface modification strategy and preparation method and application thereof
Patent Information
- Application Number
- CN202611060834.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-16
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]现有技术中,铅锡混合钙钛矿太阳能电池普遍采用直接在空穴传输层上旋涂钙钛矿前驱液、再经一步或两步退火成膜的制备工艺,主要通过优化前驱体组分(如添加SnF2)、调控退火条件来改善薄膜质量,并未采用一体化的埋底界面修饰策略,无法实现空穴传输层、埋底界面、钙钛矿体相的协同改性:既未对界面能级进行针对性调控,界面势垒高、空穴提取效率低,也未对界面缺陷进行钝化处理,界面处存在大量未配位缺陷位点成为电荷复合中心;同时,钙钛矿直接在空穴传输层上成膜,缺乏界面诱导结晶调控,界面处晶核不均、晶粒尺寸小,薄膜整体结晶质量差,且界面缺乏物理隔离层,Sn2+易被氧化、铅锡离子易发生迁移偏析,导致器件长期工作中性能快速衰减;这些单一优化手段仅能从钙钛矿本体层面缓解部分问题,无法同时解决能级失配、结晶质量差、缺陷多、电荷复合严重、稳定性差等多项界面瓶颈,更无法实现协同改性,导致器件始终难以同时兼顾低毒性、高结晶质量、高稳定性与高光电转换效率
本发明通过在钙钛矿层与空穴传输层之间的埋底界面引入2,5-二氨基苯磺酸或3,4-二氨基苯磺酸作为修饰剂进行原位改性,采用一体化的埋底界面修饰策略,实现了空穴传输层、埋底界面和钙钛矿体相的协同改性。其中修饰剂分子中的强极性磺酸基与空穴传输层中的PEDOT:PSS在界面诱导锚定形成定向分子偶极矩,通过偶极效应有效调控埋底界面的表面功函数,诱导钙钛矿界面能带发生向下弯曲,有效纠正了原本存在的能级失配,显著减小了空穴传输层与钙钛矿价带间的界面能级差,降低了光生空穴的跨界面传输势垒,从而使空穴的抽取与传输效率大幅提升。同时,修饰剂在埋底界面形成的纳米级改性层能调节衬底浸润性并提供优质异质成核位点,引导钙钛矿前驱体在界面优先成核结晶,并通过修饰剂中的氨基、磺酸基与钙钛矿前驱体发生配位作用,有效调控铅锡组分的结晶速率差异,抑制Sn组分过快结晶,使薄膜呈现强(100)/(200)晶面择优取向,晶粒更规整、致密性更高、针孔与裂纹等缺陷显著减少。在此结晶过程中,修饰剂分子利用特定取向的氨基和磺酸基还与钙钛矿前驱体溶液(甲脒碘化胺、甲基碘化胺、碘化铅、碘化亚锡和氟化亚锡)中未配位的Pb2+/Sn2+发生强配位相互作用,进而钝化埋底界面与体相的铅/锡空位缺陷、悬挂键缺陷,减少缺陷态密度,从而抑制非辐射复合中心形成,与此同时该配位作用还抑制Sn2+氧化与离子迁移偏析,避免钙钛矿组分不均。优化的能级匹配降低了电荷传输势垒,加快了光生载流子的提取与传输,结合缺陷钝化,显著降低电荷复合速率,减少了载流子复合损失。前驱体中的2-氨基-3-巯基丙酸盐酸盐通过配位抑制离子团聚,提升其稳定性;通过EDAI2与4F-PEACl分步界面修饰,同步改善了结晶质量、钝化缺陷并调控能级匹配。综上本发明制得的铅锡混合钙钛矿太阳能电池能够兼顾低毒性、高结晶质量、高稳定性并显著提升光电转换效率,更好地适配产业化与市场应用需求。
Smart Images

Figure CN122935112A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of perovskite solar cell technology, and specifically relates to a lead-tin hybrid perovskite solar cell based on a buried interface modification strategy, its preparation method, and its application. Background Technology
[0002] Perovskite materials have become a research hotspot in the fields of new energy and optoelectronic information due to their advantages such as tunable bandgap, high light absorption coefficient, high carrier mobility, and simple preparation process, showing great application potential in devices such as solar cells, photodetectors, and light-emitting diodes. Among them, lead-tin hybrid perovskite materials can combine the high stability of pure lead perovskite with the low toxicity and narrow bandgap of pure tin perovskite, making them a core material system for realizing high-efficiency tandem solar cells and low-toxicity optoelectronic devices.
[0003] However, the industrialization of lead-tin hybrid perovskite solar cells still faces many key bottlenecks: the buried interface between the perovskite layer and the hole transport layer, as the core channel for the extraction, separation, and transport of photogenerated carriers, is also a major area for defect enrichment, charge recombination, and ion migration, and is generally characterized by lead-tin ion migration and segregation, Sn... 2+ Problems such as easy oxidation, high interface defect density, energy level mismatch, and poor crystal quality can easily lead to severe interface charge recombination, which directly restricts the improvement of the device's photoelectric conversion efficiency and long-term stability, becoming a key obstacle to its performance breakthrough.
[0004] In existing technologies, lead-tin hybrid perovskite solar cells generally employ a fabrication process involving spin-coating a perovskite precursor solution directly onto the hole transport layer, followed by one or two-step annealing to form the film. The quality of the perovskite film is improved solely by optimizing the precursor composition (e.g., adding SnF2) and controlling the annealing temperature and atmosphere. This type of process can only alleviate the Sn problem to a limited extent at the perovskite bulk level. 2+ The problems of oxidation and crystallization defects (perovskite film quality) still lack targeted control over the buried interface: it is impossible to effectively passivate uncoordinated defect sites at the interface, it is difficult to suppress the interfacial migration and segregation of lead-tin ions, and it is impossible to accurately optimize the interfacial energy level matching relationship, resulting in severe interfacial charge recombination losses. Therefore, existing fabrication processes cannot fundamentally solve the inherent defects of the buried interface, making it difficult to simultaneously achieve low toxicity, high crystallinity, and high stability of the device, and also difficult to achieve a significant improvement in photoelectric conversion efficiency. New technical solutions are urgently needed to overcome this bottleneck. Summary of the Invention
[0005] In existing technologies, lead-tin hybrid perovskite solar cells generally employ a fabrication process involving spin-coating a perovskite precursor solution directly onto the hole transport layer, followed by one or two-step annealing to form the film. The quality of the film is primarily improved by optimizing the precursor composition (e.g., adding SnF2) and controlling the annealing conditions. However, an integrated buried interface modification strategy is not adopted, failing to achieve synergistic modification of the hole transport layer, buried interface, and perovskite bulk phase. Specifically, the interface energy levels are not specifically controlled, resulting in high interface barriers and low hole extraction efficiency. Furthermore, interface defects are not passivated, leading to numerous uncoordinated defect sites at the interface that become charge recombination centers. Simultaneously, the direct formation of the perovskite film on the hole transport layer lacks interface-induced crystallization control, resulting in uneven nuclei and small grain sizes at the interface, leading to poor overall film crystallization quality. Additionally, the interface lacks a physical isolation layer, hindering the development of a comprehensive perovskite-based solar cell. 2+ The perovskite is easily oxidized, and lead-tin ions are prone to migration and segregation, leading to rapid performance degradation of the device during long-term operation. These single optimization methods can only alleviate some problems at the perovskite bulk level, and cannot simultaneously solve multiple interface bottlenecks such as energy level mismatch, poor crystal quality, many defects, severe charge recombination, and poor stability. Furthermore, they cannot achieve synergistic modification, making it difficult for the device to simultaneously achieve low toxicity, high crystal quality, high stability, and high photoelectric conversion efficiency.
[0006] To address the aforementioned technical problems, this invention provides a lead-tin hybrid perovskite solar cell based on a buried interface modification strategy. This lead-tin hybrid perovskite solar cell, from bottom to top, comprises a conductive substrate, a hole transport layer, a buried interface modification layer, a perovskite light-absorbing layer, an electron transport layer, and a metal electrode; wherein: A hole transport solution is spin-coated onto a conductive substrate that has been treated with ultraviolet ozone, and then annealed to obtain a hole transport layer. The hole transport solution is poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS). A 2,5-diaminobenzenesulfonic acid solution or a 3,4-diaminobenzenesulfonic acid solution is spin-coated onto the hole transport layer and then annealed to obtain a buried interface modification layer. The perovskite precursor solution, ethylenediamine dihydroiodide solution, and 4-fluorophenylethylamine chloride solution were sequentially spin-coated onto the buried interface modification layer and then sequentially annealed to obtain the perovskite light-absorbing layer. The perovskite precursor solution was prepared by dissolving formamidine iodide, methyl iodide, lead iodide, stannous iodide, and stannous fluoride in a polar organic solvent, stirring until completely dissolved, and then adding 2-amino-3-mercaptopropionate. An electron transport layer was prepared by spin-coating a fullerene derivative and 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline onto a perovskite light-absorbing layer using a thermal evaporation method. A lead-tin hybrid perovskite solar cell was obtained by thermally evaporating a metal electrode onto the electron transport layer.
[0007] By applying either 2,5-diaminobenzenesulfonic acid or 3,4-diaminobenzenesulfonic acid to modify the buried interface of lead-tin mixed perovskites, the core challenges of the buried interface are simultaneously addressed from three dimensions: nucleation and crystallization, defect passivation, and ion stabilization, through in-situ interface modification and synergistic regulation of the perovskite precursor. Specifically, benzenesulfonic acid molecules can construct a uniform ultrathin modification layer at the buried interface. The dual active functional groups of amino (-NH2) and sulfonic acid (-SO3H) groups within the molecule can interact with Pb at the buried interface. 2+ Sn 2+ Strong coordination bonds are formed. On the one hand, this precisely anchors metal ions at the interface, effectively suppressing Sn at the buried interface. 2+ The oxidation of this molecule can alleviate the segregation behavior of lead and tin ions at the interface, significantly reduce the antisite defects and vacancy defects of lead and tin ions at the interface, and fundamentally reduce the defect state density of the buried interface. On the other hand, it can serve as a high-quality heterogeneous nucleation site at the buried interface, precisely regulate the crystallization kinetics of perovskite at the interface, reduce the difference in crystallization rate between Pb and Sn ions, solve the industry problem of asynchronous crystallization at the interface, promote the uniform and orderly distribution of lead and tin ions at the interface, suppress interfacial phase separation, and ultimately form a dense, low-defect, high-quality interfacial crystalline structure. In addition, this molecule can also optimize the energy level matching state of the buried interface, reduce the interfacial charge transport barrier, significantly suppress nonradiative recombination at the interface, and greatly improve the separation and transport efficiency of charge carriers at the buried interface.
[0008] The perovskite light-absorbing layer was prepared by annealing a perovskite precursor solution, an ethylenediamine dihydroiodide (EDAI2) solution, and a 4-fluorophenylethylamine chloride (4F-PEACl) solution sequentially spin-coated onto a buried interface modification layer. The perovskite precursor solution was prepared by dissolving formammonium iodide (FAI), methylammonium iodide (MAI), lead iodide (PbI2), stannous iodide (SnI2), and stannous fluoride (SnF2) in a polar organic solvent, stirring until completely dissolved, and then adding 2-amino( ... It is prepared by 3-mercaptopropionate (AMPH); this perovskite light-absorbing layer serves as the core photoactive layer of the device, which can efficiently capture incident sunlight and generate and transport photogenerated carriers; at the same time, by using stepwise interface modification of EDAI2 and 4F-PEACl, the perovskite crystal quality can be optimized, intrinsic defects can be passivated, and interface energy level matching can be controlled simultaneously, which significantly improves the photogenerated carrier separation efficiency and the long-term stability of the perovskite film, providing core functional guarantee for the efficient photoelectric conversion of solar cells.
[0009] AMPH can bind metal ions through coordination, inhibit ion aggregation, stabilize precursor solutions, optimize solution spreadability, pre-passivate film defects, regulate crystal growth, and suppress phase separation, thus contributing to the preparation of high-quality perovskite films.
[0010] The electron transport layer is prepared by thermal evaporation of fullerene derivatives and 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP) sequentially spin-coated onto the perovskite light-absorbing layer; the metal electrode is prepared by thermal evaporation on the electron transport layer.
[0011] In the lead-tin hybrid perovskite solar cell of this invention, the synergistic modification effect of the buried interface is particularly crucial, addressing the core interface challenges from two dimensions: Firstly, after modification and regulation, the lead-tin hybrid perovskite crystals are more uniformly crystallized, and interface defects are significantly reduced, enabling the formation of a dense and well-fitting contact structure at the buried interface. This effectively lowers the charge transport barrier, significantly improves the separation and transport efficiency of photogenerated carriers, and reduces carrier accumulation and non-radiative recombination at the interface. Secondly, the Sn at the interface... 2+ The oxidation of Sn is effectively inhibited, thus avoiding Sn oxidation. 4+ Oxidation products accumulate at the interface, preventing obstruction of charge transport channels and ensuring the stability and efficiency of carrier transport. Based on this synergistic interface modification, the photoelectric conversion efficiency of the battery is significantly improved, its environmental stability is enhanced, its lifespan is extended, and it better meets the needs of green energy development.
[0012] In addition, the efficient modification of the buried interface can significantly improve the photoelectric conversion efficiency and operational stability of the battery, resulting in better device safety. When this material is extended to other optoelectronic devices, the synergistic regulation of the buried interface also plays a key role, such as improving the response speed of multi-band photodetectors, reducing non-radiative recombination at the interface of LED light-emitting devices, and ensuring the carrier transport stability of field-effect transistors, further broadening the application scenarios of the material.
[0013] Modification and enhancement of the buried interface are equally crucial, addressing the core issues of poor contact and impeded charge transport at the buried interface. The integrated buried interface modification strategy proposed in this invention simultaneously achieves synergistic modification of the hole transport layer, buried interface, and perovskite bulk phase. Specifically, the perovskite material optimizes the structural arrangement of the buried interface, enhancing its charge transport capability. Simultaneously, it adjusts the bonding state between the perovskite and the buried interface, reducing non-radiative recombination losses and contributing to the formation of a uniform and dense crystal structure. This structurally ensures the continuous stability of carrier transport at the buried interface, avoiding interface transport losses caused by thin film defects. Furthermore, by optimizing the contact state, charge transport barrier, and interface stability between the perovskite and the buried interface, while simultaneously improving the contact characteristics between the hole transport layer and the interface and lowering the charge transport barrier, the hole extraction and transport efficiency of the buried interface can be maximized, laying a solid interfacial foundation for high-performance devices. This promotes uniform growth of perovskite crystals and reduces non-radiative recombination at the interface. At the same time, it enhances the crystallinity and stability of the perovskite bulk phase. These three factors work synergistically to maximize hole extraction and transport efficiency, ensuring high-performance devices.
[0014] This lead-tin hybrid perovskite material also has broad application prospects in the field of optoelectronic information functional materials: in high-sensitivity multi-band photodetectors, efficient charge transport at the buried interface can significantly improve the detection response speed; in low-toxicity, tunable wavelength, high-efficiency LED light-emitting devices, it can effectively reduce non-radiative recombination at the buried interface and improve luminous efficiency; in high-performance field-effect transistors that balance carrier mobility and stability, it can maintain the carrier mobility at the buried interface, ensuring the long-term stability of the device's switching performance, further expanding the material's practical application value.
[0015] Preferably, the mass concentrations of both the 2,5-diaminobenzenesulfonic acid solution and the 3,4-diaminobenzenesulfonic acid solution are 0.1 mg / mL to 2 mg / mL. Both solutions are prepared from a 1:1 volume ratio of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO). This concentration range ensures uniform dispersion of the modifier in the mixed solvent, resulting in a controllable, continuous, and dense ultrathin modified layer at the substrate interface after spin coating. Concentrations below 0.1 mg / mL result in insufficient interface coverage and limited defect passivation; concentrations above 2 mg / mL tend to form an excessively thick organic deposit, increasing the charge transport barrier and inducing perovskite growth defects. This preferred concentration balances the uniformity of the modified layer, passivation effect, and charge transport performance, providing an ideal interface for subsequent perovskite film growth.
[0016] Modifying the buried interface with either 2,5-diaminobenzenesulfonic acid or 3,4-diaminobenzenesulfonic acid, combined with the synergistic regulation of the lead-tin mixed perovskite precursor, can effectively repair defects in lead-tin mixed perovskite films and inhibit Sn. 2+ Oxidation and optimization of the interfacial arrangement of lead-tin ions. Specifically, in the preparation of lead-tin mixed perovskite films, p-aminobenzenesulfonic acid is used as a buried interface modifier to inhibit Sn ion oxidation and optimize the interfacial arrangement of lead-tin ions. 2+ Oxidation can regulate the interfacial growth rate of lead-tin mixed crystals, improving problems such as uneven film formation and the occurrence of pinholes or phase separation. This type of interface optimization can fundamentally solve the core pain points of poor contact and obstructed charge transport at the buried interface of traditional perovskites, avoiding interfacial carrier transport losses caused by film defects, while also addressing industry challenges such as the high toxicity of pure lead perovskites and the insufficient photoelectric efficiency of pure tin perovskites.
[0017] Preferably, the spin coating speed of the 2,5-diaminobenzenesulfonic acid solution or the 3,4-diaminobenzenesulfonic acid solution is 2000 rpm to 5000 rpm, the spin coating time is 20 s to 40 s, the annealing temperature is 100 ℃ to 200 ℃, and the annealing time is 1 min to 5 min.
[0018] The spin coating speed and time were chosen to form an ultra-thin, uniform, and continuous modification layer, avoiding excessive agglomeration due to excessive thickness or discontinuous layers due to excessive thinness, thus providing a stable substrate for perovskite crystallization. The temperature and time were selected to thoroughly remove solvent residue, ensuring stable anchoring and effective function of the modifier, while avoiding high-temperature damage to the interface and underlying structure.
[0019] Preferably, the spin-coating material on the hole transport layer is poly(3,4-ethylenedioxythiophene)polystyrene sulfonate (PEDOT:PSS), and the mass fraction of PEDOT:PSS in the PEDOT:PSS solution is 1.0%–1.5%. This material is chosen because it possesses excellent conductivity and energy level matching, enabling efficient hole transport from the perovskite layer and reducing interfacial charge recombination. Simultaneously, it improves the wettability of the buried interface, providing an ideal substrate for perovskite film growth, reducing film formation defects, and is highly compatible with solution spin-coating processes, making it suitable for large-scale fabrication. Due to its excellent light transmittance, conductivity, and good energy level matching, PEDOT:PSS effectively reduces interfacial carrier recombination, improving the crystallinity of the perovskite film and the overall stability of the device.
[0020] Preferably, the spin coating speed of the hole transport fluid is 3000 rpm to 6000 rpm, the spin coating time is 20 s to 40 s, the annealing temperature is 100 ℃ to 200 ℃, and the annealing time is 10 min to 30 min.
[0021] The rotation speed range was selected to precisely control the optimal thickness of the hole transport layer, avoiding excessive thickness leading to increased resistance or insufficient thickness resulting in uneven coverage, thus optimizing the film density. The annealing temperature range was selected to thoroughly remove moisture and residual solvents to prevent subsequent film cracking and improve conductivity, while avoiding excessively low temperatures that could lead to solvent residue or excessively high temperatures that could cause material decomposition, thereby ensuring charge transport efficiency and reducing interfacial charge load.
[0022] Preferably, the molar ratio of formamidinium iodide, methyl iodide, lead iodide, stannous iodide, and stannous fluoride is 0.7:0.3:0.5:0.5:0.1, and the amount of 2-amino-3-mercaptopropionate added is 2 mg / ml, the concentration of the perovskite precursor solution is 0.6 mol / L to 1.8 mol / L, the concentration of the ethylenediamine dihydroiodide solution is 0.2 mg / ml to 2 mg / ml, and the concentration of the 4-fluorophenylethylamine chloride solution is 0.2 mg / ml to 2 mg / ml. The polar organic solvent is a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide, and the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide is 3:1.
[0023] In the perovskite precursor solution, the general chemical formula of the perovskite precursor is AB1Y1Y2Y3 or AB1B2Y1Y2Y3, where A is selected from formamidinium cation (FA). + ), methylamine cation (MA) + ), cesium ions (Cs) + B1 is at least one of the following: B1 is a tin ion (Sn). 2 + B2 is lead ion (Pb) 2+ Y1, Y2, and Y3 are each an independent halide ion. Simultaneously, 2-amino-3-mercaptopropionate (AMPH) is introduced into the perovskite precursor solution. This additive can enhance the stability of the precursor solution by forming coordination interactions with metal ions in the system, inhibiting ion aggregation, optimizing the spreading and wetting properties of the solution on the substrate surface to form a uniform and dense film, pre-passivating intrinsic defects in perovskite, and precisely controlling crystal growth kinetics, thus ensuring the controllable preparation of high-quality perovskite films.
[0024] DMF can efficiently dissolve organic cationic salts (formamidinium iodide, methyl iodide) and lead iodide (PbI2), while DMSO can enhance the solubility and coordination of tin-based components. The two work together to regulate the solvent evaporation rate to promote the ordered crystallization of perovskite. At the same time, they are adapted to spin coating processes to optimize the uniformity and density of the film, thereby ensuring the high crystallinity and low defect state of lead-tin mixed perovskite films.
[0025] Preferably, the spin-coating and annealing steps of the perovskite precursor solution, ethylenediamine diiodide, and 4-fluorophenylethylamine chloride solution are as follows: The perovskite precursor solution was first spin-coated onto a conductive substrate with a pre-deposited hole transport layer at a speed of 1000 rpm to 2000 rpm for 10 to 15 s, and then spin-coated at a speed of 3000 rpm to 7000 rpm for 20 to 50 s for annealing. Then, ethylenediamine diiodide and 4-fluorophenylethylamine chloride solutions were spin-coated at a speed of 4000 rpm to 6000 rpm for 20 to 30 s, and then annealed. The temperature of each annealing treatment was 60℃ to 120℃, and the annealing time was 1 min to 10 min.
[0026] The perovskite precursor solution is first spin-coated at 1000-2000 rpm for 10-15 seconds to ensure uniform spread of the precursor and thorough wetting of the hole transport layer. Then, it is spin-coated at 3000-7000 rpm for 20-50 seconds to precisely control the perovskite layer thickness and promote solvent evaporation and crystallization, avoiding problems such as film discontinuity and excessive defects. Ethylenediamine diiodide and 4-fluorophenylethylamine chloride are spin-coated at 4000-6000 rpm for 20-30 seconds to form a thin and uniform modification layer, balancing spread uniformity and solvent evaporation efficiency. This avoids problems such as an excessively thin modification layer failing to cover defects or an excessively thick layer introducing transport barriers and solvent residue leading to aggregation. The core function of annealing at 60℃~120℃ is to improve the perovskite crystal structure, eliminate defects and enhance interfacial bonding. Controlling the annealing time is to avoid insufficient crystallization in a short time or excessive crystallization in a long time. Therefore, the annealing time parameter is limited to 1min~10min, which is the optimal choice to balance crystallization quality and material stability.
[0027] Preferably, the fullerene derivative is C 60 The thermally vapor-deposited metal electrode on the electron transport layer is a copper electrode.
[0028] Choosing C60 and copper electrodes is an optimized choice considering energy level matching, transport efficiency, device stability, process compatibility, and cost, balancing the photoelectric performance of the battery with its potential for large-scale application. Preferably, the conductive substrate includes a substrate and a transparent electrode, wherein the transparent electrode is indium tin oxide (ITO).
[0029] This invention provides a method for fabricating lead-tin hybrid perovskite solar cells based on a buried interface modification strategy.
[0030] This invention also provides an application of lead-tin hybrid perovskite solar cells based on a buried interface modification strategy in optoelectronic devices.
[0031] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention introduces 2,5-diaminobenzenesulfonic acid or 3,4-diaminobenzenesulfonic acid as a modifier at the buried interface between the perovskite layer and the hole transport layer for in-situ modification. Employing an integrated buried interface modification strategy, it achieves synergistic modification of the hole transport layer, the buried interface, and the perovskite bulk phase. Specifically, the strongly polar sulfonic acid groups in the modifier molecules and PEDOT:PSS in the hole transport layer induce an anchoring at the interface, forming a directional molecular dipole moment. This dipole effect effectively modulates the surface work function of the buried interface, inducing downward bending of the perovskite interface bands. This effectively corrects the existing energy level mismatch, significantly reduces the interfacial energy level difference between the hole transport layer and the perovskite valence band, lowers the cross-interface transport barrier for photogenerated holes, and thus greatly improves the hole extraction and transport efficiency. Meanwhile, the nanoscale modified layer formed by the modifier at the buried interface can regulate the substrate wettability and provide high-quality heterogeneous nucleation sites, guiding the perovskite precursor to preferentially nucleate and crystallize at the interface. Through the coordination of the amino and sulfonic acid groups in the modifier with the perovskite precursor, the difference in crystallization rate of lead and tin components is effectively controlled, and the excessively rapid crystallization of Sn components is inhibited, so that the film exhibits a strong (100) / (200) crystal plane preferred orientation, the grains are more regular, the density is higher, and defects such as pinholes and cracks are significantly reduced. During this crystallization process, the modifier molecules also use the specifically oriented amino and sulfonic acid groups to react with the uncoordinated Pb in the perovskite precursor solution (formamidinium iodide, methyl iodide, lead iodide, stannous iodide, and stannous fluoride). 2+ / Sn 2+ Strong coordination interactions occur, which passivate lead / tin vacancy defects and dangling bond defects at the buried interface and in the bulk phase, reducing the defect state density and thus inhibiting the formation of nonradiative recombination centers. Simultaneously, this coordination effect also inhibits Sn... 2+ Oxidation and ion migration segregation prevent perovskite compositional inhomogeneity. Optimized energy level matching lowers the charge transport barrier, accelerating the extraction and transport of photogenerated carriers. Combined with defect passivation, this significantly reduces the charge recombination rate and minimizes carrier recombination losses. The 2-amino-3-mercaptopropionate in the precursor inhibits ion aggregation through coordination, enhancing its stability. Stepwise interface modification with EDAI2 and 4F-PEACl simultaneously improves crystal quality, passivates defects, and modulates energy level matching. In summary, the lead-tin hybrid perovskite solar cell prepared by this invention achieves a balance of low toxicity, high crystal quality, high stability, and significantly improved photoelectric conversion efficiency, better meeting the needs of industrialization and market applications. Attached Figure Description
[0032] Figure 1 This is a schematic diagram of the perovskite solar cell structure in Embodiment 1 of the present invention.
[0033] Figure 2 This is a schematic diagram of the structural composition of the perovskite solar cell in Embodiment 1 of the present invention.
[0034] Figure 3 The image shows the atomic force microscopy test results of the lead-tin mixed perovskite thin film in Comparative Example 1 of this invention.
[0035] Figure 4 The image shows the atomic force microscopy test results of the lead-tin mixed perovskite thin film in Example 1 of the present invention, where 3,4-SA is 3,4-diaminobenzenesulfonic acid.
[0036] Figure 5 The images show the X-ray diffraction test results of the lead-tin mixed perovskite films in Example 1 and Comparative Example 1 of this invention.
[0037] Figure 6 The graph shows the electrochemical impedance test results of the perovskite solar cells in Example 1 and Comparative Example 1 of this invention.
[0038] Figure 7 The figures show the long-term stability test curves of the perovskite solar cells in Example 1 and Comparative Example 1 of this invention under a nitrogen glove box environment. Detailed Implementation
[0039] The specific embodiments of the present invention are described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention. Unless otherwise specified, the experimental methods described in the embodiments of the present invention are conventional methods.
[0040] It should be noted that when numerical ranges are involved in this invention, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as in Examples 1 to 8, preferred embodiments are described in this invention to avoid redundancy. However, this invention is not limited to these, but can be specifically implemented in other ways within the scope of the technical solutions defined in the appended claims. All raw materials, reagents, instruments, and equipment used in the following embodiments of this invention can be purchased from the market or prepared by existing methods.
[0041] The following detailed description, in conjunction with embodiments of the present invention and accompanying drawings, provides a clear and complete illustration of the technical solutions in these embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0042] Unless otherwise specified, the experimental methods described in the following examples are generally performed under conventional conditions in the art or as recommended by the manufacturer; the raw materials and reagents used are all commercially available from the conventional market unless otherwise specified.
[0043] Example 1 A method for fabricating a lead-tin hybrid perovskite solar cell based on a buried interface modification strategy includes the following steps: (1) Treatment of glass substrates with deposited ITO (hereinafter referred to as ITO glass substrates) The ITO glass substrate underwent continuous multi-step ultrasonic cleaning. In each ultrasonic cleaning tank, cleaning agent, deionized water, acetone, and ethanol were added sequentially. After ultrasonic cleaning, the ITO glass substrate was dried. The cleaned ITO glass substrate was then subjected to ultraviolet (UV) irradiation. The ITO glass substrate had a transmittance of 90%, an impedance of 15 ohms, and was purchased from a reputable supplier; model number 1.1mm 15 ohms.
[0044] (2) Preparation of hole transport layer The filtered poly(3,4-ethylenedioxythiophene)polystyrene sulfonate (PEDOT:PSS) solution was spin-coated onto the ITO substrate at 6000 rpm for 30 seconds to form a uniform film. It was then immediately transferred to a hot plate and annealed at 150°C for 20 minutes to remove residual solvent and improve film density. After the substrate cooled naturally to room temperature, it was transferred into a nitrogen glove box for subsequent experiments.
[0045] (3) Preparation of the buried interface modification layer An additive solution containing 3,4-diaminobenzenesulfonic acid (concentration of 1.5 mg / mL, solvent is a 1:1 volume mixture of DMF and DMSO) was spin-coated onto the hole transport layer at a speed of 5000 rpm for 30 s. Then it was placed on a hot plate and annealed at 100 °C for 5 minutes to promote solvent evaporation and induce the modified layer molecules to align on the substrate surface.
[0046] (4) Preparation of perovskite light-absorbing layer Then, in the glove box, the perovskite precursor was first spin-coated onto the subsurface interface modification layer in two steps and then annealed to prepare the perovskite substrate. The perovskite material selected was FA. 0.7 MA 0.3 Pb 0.5 Sn 0.5 I 3。Weigh out formamidinium iodide, methyl iodide, lead iodide, stannous iodide, and stannous fluoride in a molar ratio of 0.7:0.3:0.5:0.5:0.1. Dissolve the formamidinium iodide, methyl iodide, lead iodide, stannous iodide, and stannous fluoride in an organic polar solvent of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 3:1. Stir until completely dissolved, and then add 2 mg / ml of 2-amino-3-mercaptopropionate to prepare a 1.8 mol / L perovskite precursor solution.
[0047] The spin coating speed of the perovskite precursor solution in the first stage (first step) was controlled at 1000 rpm, the acceleration was 1000 rpm / s, and the spin coating time was 10s. In the second stage (step 2), the spin coating speed of the perovskite precursor solution was controlled at 4000 rpm, the acceleration at 5000 rpm / s, and the spin coating time at 40 s, followed by annealing at 100℃ for 10 min to complete the preparation of the perovskite substrate.
[0048] Subsequently, a 2 mg / ml EDAI2 solution was spin-coated onto the perovskite substrate surface at a spin-coating rate of 5000 rpm for 30 seconds, followed by annealing at 100°C for 5 minutes. Then, a 2 mg / ml 4F-PEACl solution was spin-coated onto the surface at a spin-coating rate of 5000 rpm for 30 seconds, followed by annealing at 100°C for 5 minutes to complete the preparation of the perovskite passivation layer, thus obtaining the perovskite light-absorbing layer.
[0049] (5) Fabrication of electron transport layer After spin-coating the perovskite light-absorbing layer (perovskite passivation layer surface), under a vacuum degree <10 -5 Under the conditions of Pa, a fullerene layer with a thickness of 40 nm was sequentially deposited by thermal evaporation at a thermal evaporation rate of 0.5 nm / s. 60 A BCP interface modification layer with a thickness of 8 nm was added to complete the preparation of the electron transport layer modification layer (buffer layer).
[0050] A copper (Cu) electrode was thermally deposited on the electron transport layer (buffer layer) at a thermal evaporation rate of 1 nm / s, resulting in a copper (Cu) electrode deposition thickness of 100 nm. This ultimately led to the fabrication of a lead-tin hybrid perovskite solar cell, such as... Figure 1 and Figure 2 As shown.
[0051] Example 2 A method for fabricating a lead-tin hybrid perovskite solar cell based on a buried interface modification strategy includes the following steps: (1) Treatment of glass substrates with deposited ITO (hereinafter referred to as ITO glass substrates) The ITO glass substrate underwent continuous multi-step ultrasonic cleaning. In each ultrasonic cleaning tank, cleaning agent, deionized water, acetone, and ethanol were added sequentially. After ultrasonic cleaning, the ITO glass substrate was dried. The cleaned ITO glass substrate was then subjected to ultraviolet (UV) irradiation. The ITO glass substrate had a transmittance of 90%, an impedance of 15 ohms, and was purchased from a reputable supplier; model number 1.1mm 15 ohms.
[0052] (2) Preparation of hole transport layer The filtered poly(3,4-ethylenedioxythiophene)polystyrene sulfonate (PEDOT:PSS) solution was spin-coated onto the surface of an ITO substrate at 3000 rpm for 20 seconds to form a uniform film. It was then immediately transferred to a hot plate and annealed at 100°C for 30 minutes to remove residual solvent and improve the film density. After the substrate cooled naturally to room temperature, it was transferred into a nitrogen glove box for subsequent experiments.
[0053] (3) Preparation of the buried interface modification layer An additive solution containing 3,4-diaminobenzenesulfonic acid (concentration of 0.1 mg / mL, solvent is a 1:1 volume mixture of DMF and DMSO) was spin-coated onto the hole transport layer at 3000 rpm for 20 s. Then it was placed on a hot plate and annealed at 200 °C for 3 minutes to promote solvent evaporation and induce the modified layer molecules to oriented on the substrate surface.
[0054] (4) Preparation of perovskite light-absorbing layer Then, in the glove box, the perovskite precursor was first spin-coated onto the subsurface interface modification layer in two steps and then annealed to prepare the perovskite substrate. The perovskite material selected was FA. 0.7 MA 0.3 Pb 0.5 Sn 0.5 I 3。 Weigh out formamidinium iodide, methyl iodide, lead iodide, stannous iodide, and stannous fluoride in a molar ratio of 0.7:0.3:0.5:0.5:0.1. Dissolve the formamidinium iodide, methyl iodide, lead iodide, stannous iodide, and stannous fluoride in an organic polar solvent of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 3:1. Stir until completely dissolved, and then add 3 mg / ml of 2-amino-3-mercaptopropionate to prepare a 1.0 mol / L perovskite precursor solution.
[0055] The spin coating speed of the perovskite precursor solution in the first stage (first step) was controlled at 2000 rpm, the acceleration was 1000 rpm / s, and the spin coating time was 15s. In the second stage (step 2), the spin coating speed of the perovskite precursor solution was controlled at 3000 rpm, the acceleration at 5000 rpm / s, and the spin coating time at 20 s, followed by annealing at 60℃ for 5 min to complete the preparation of the perovskite layer substrate.
[0056] Subsequently, a 0.2 mg / ml EDAI2 solution was spin-coated onto the perovskite substrate surface at a spin-coating rate of 4000 rpm for 20 seconds, followed by annealing at 60°C for 10 minutes. Then, a 1 mg / ml 4F-PEACl solution was spin-coated onto the surface at a spin-coating rate of 4000 rpm for 20 seconds, followed by annealing at 60°C for 10 minutes to complete the preparation of the perovskite passivation layer, thus obtaining the perovskite light-absorbing layer.
[0057] (5) Fabrication of electron transport layer After spin-coating the perovskite light-absorbing layer (perovskite passivation layer surface), under a vacuum degree <10 -5 Under the conditions of Pa, a fullerene layer with a thickness of 40 nm was sequentially deposited by thermal evaporation at a thermal evaporation rate of 0.5 nm / s. 60 A BCP interface modification layer with a thickness of 8 nm was added to complete the preparation of the electron transport layer modification layer (buffer layer).
[0058] A copper (Cu) electrode was thermally deposited on the electron transport layer (buffer layer) at a thermal evaporation rate of 1 nm / s, resulting in a copper (Cu) electrode deposition thickness of 100 nm. This ultimately led to the fabrication of a lead-tin hybrid perovskite solar cell, such as... Figure 1 and Figure 2 As shown.
[0059] Example 3 A method for fabricating a lead-tin hybrid perovskite solar cell based on a buried interface modification strategy includes the following steps: (1) Treatment of glass substrates with deposited ITO (hereinafter referred to as ITO glass substrates) The ITO glass substrate underwent continuous multi-step ultrasonic cleaning. In each ultrasonic cleaning tank, cleaning agent, deionized water, acetone, and ethanol were added sequentially. After ultrasonic cleaning, the ITO glass substrate was dried. The cleaned ITO glass substrate was then subjected to ultraviolet (UV) irradiation. The ITO glass substrate had a transmittance of 90%, an impedance of 15 ohms, and was purchased from a reputable supplier; model number 1.1mm 15 ohms.
[0060] (2) Preparation of hole transport layer The filtered poly(3,4-ethylenedioxythiophene)polystyrene sulfonate (PEDOT:PSS) solution was spin-coated onto the ITO substrate at 4000 rpm for 40 seconds to form a uniform film. It was then immediately transferred to a hot plate and annealed at 200°C for 10 minutes to remove residual solvent and improve film density. After the substrate cooled to room temperature naturally, it was transferred into a nitrogen glove box for subsequent experiments.
[0061] (3) Preparation of the buried interface modification layer An additive solution containing 3,4-diaminobenzenesulfonic acid (concentration of 2.0 mg / mL, solvent is a 1:1 volume mixture of DMF and DMSO) was spin-coated onto the hole transport layer at a speed of 2000 rpm for 40 s. Then it was placed on a hot plate and annealed at 150 °C for 1 minute to promote solvent evaporation and induce the modified layer molecules to oriented on the substrate surface.
[0062] (4) Preparation of perovskite light-absorbing layer Then, in the glove box, the perovskite precursor was first spin-coated onto the subsurface interface modification layer in two steps and then annealed to prepare the perovskite substrate. The perovskite material selected was FA. 0.7 MA 0.3 Pb 0.5 Sn 0.5 I 3。 Weigh out formamidinium iodide, methyl iodide, lead iodide, stannous iodide, and stannous fluoride in a molar ratio of 0.7:0.3:0.5:0.5:0.1. Dissolve the formamidinium iodide, methyl iodide, lead iodide, stannous iodide, and stannous fluoride in an organic polar solvent of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 3:1. Stir until completely dissolved, then add 0.5 mg / ml of 2-amino-3-mercaptopropionate to prepare a 0.6 mol / L perovskite precursor solution.
[0063] The spin-coating speed of the perovskite precursor solution in the first stage (first step) was controlled at 1500 rpm, the acceleration was 1000 rpm / s, and the spin-coating time was 12s. The spin-coating speed of the perovskite precursor solution in the second stage (step 2) was controlled at 7000 rpm, the acceleration at 5000 rpm / s, and the spin-coating time at 50 s, followed by annealing at 120℃ for 1 min to complete the preparation of the perovskite substrate.
[0064] Subsequently, a 1 mg / ml EDAI2 solution was spin-coated onto the perovskite substrate surface at a spin-coating rate of 6000 rpm for 25 seconds, followed by annealing at 120°C for 1 minute. Then, a 0.2 mg / ml 4F-PEACl solution was spin-coated onto the surface at a spin-coating rate of 6000 rpm for 25 seconds, followed by annealing at 120°C for 1 minute to complete the preparation of the perovskite passivation layer, thus obtaining the perovskite light-absorbing layer.
[0065] (5) Fabrication of electron transport layer After spin-coating the perovskite light-absorbing layer (perovskite passivation layer surface), under a vacuum degree <10 -5 Under the conditions of Pa, a fullerene layer with a thickness of 40 nm was sequentially deposited by thermal evaporation at a thermal evaporation rate of 0.5 nm / s. 60 A BCP interface modification layer with a thickness of 8 nm was added to complete the preparation of the electron transport layer modification layer (buffer layer).
[0066] A copper (Cu) electrode was thermally deposited on the electron transport layer (buffer layer) at a thermal evaporation rate of 1 nm / s, resulting in a copper (Cu) electrode deposition thickness of 100 nm. This ultimately led to the fabrication of a lead-tin hybrid perovskite solar cell, such as... Figure 1 and Figure 2 As shown.
[0067] Example 4 The difference between Example 4 and Example 1 is that 3,4-diaminobenzenesulfonic acid is replaced with 2,5-diaminobenzenesulfonic acid.
[0068] Example 5 The difference between Example 5 and Example 2 is that 3,4-diaminobenzenesulfonic acid is replaced with 2,5-diaminobenzenesulfonic acid.
[0069] Example 6 The difference between Example 6 and Example 3 is that 3,4-diaminobenzenesulfonic acid is replaced with 2,5-diaminobenzenesulfonic acid.
[0070] Example 7 A method for fabricating a lead-tin hybrid perovskite solar cell based on a buried interface modification strategy includes the following steps: (1) Treatment of glass substrates with deposited ITO (hereinafter referred to as ITO glass substrates) The ITO glass substrate underwent continuous multi-step ultrasonic cleaning. In each ultrasonic cleaning tank, cleaning agent, deionized water, acetone, and ethanol were added sequentially. After ultrasonic cleaning, the ITO glass substrate was dried. The cleaned ITO glass substrate was then subjected to ultraviolet (UV) irradiation. The ITO glass substrate had a transmittance of 90%, an impedance of 15 ohms, and was purchased from a reputable supplier; model number 1.1mm 15 ohms.
[0071] (2) Preparation of hole transport layer The filtered poly(3,4-ethylenedioxythiophene)polystyrene sulfonate (PEDOT:PSS) solution with a concentration of 1.0–1.5 wt% was spin-coated onto the ITO substrate at 6000 rpm for 30 seconds to form a uniform film. It was then immediately transferred to a hot plate and annealed at 100°C for 10 minutes to remove residual solvent and improve the film density. After the substrate cooled naturally to room temperature, it was transferred into a nitrogen glove box for subsequent experiments.
[0072] (3) Preparation of the buried interface modification layer An additive solution containing 3,4-diaminobenzenesulfonic acid (concentration of 0.1 mg / mL, solvent is a 1:1 volume mixture of DMF and DMSO) was spin-coated onto the hole transport layer at a speed of 2000 rpm for 20 s. Then it was placed on a hot plate and annealed at 150 °C for 1 minute to promote solvent evaporation and induce the modified layer molecules to oriented on the substrate surface.
[0073] (4) Preparation of perovskite light-absorbing layer Then, in the glove box, the perovskite precursor was first spin-coated onto the subsurface interface modification layer in two steps and then annealed to prepare the perovskite substrate. The perovskite material selected was FA. 0.7 MA 0.3 Pb 0.5 Sn 0.5 I 3。 Weigh out formamidinium iodide, methyl iodide, lead iodide, stannous iodide, and stannous fluoride in a molar ratio of 0.7:0.3:0.5:0.5:0.1. Dissolve the formamidinium iodide, methyl iodide, lead iodide, stannous iodide, and stannous fluoride in an organic polar solvent of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 3:1. Stir until completely dissolved, and then add 2 mg / ml of 2-amino-3-mercaptopropionate to prepare a 1.8 mol / L perovskite precursor solution.
[0074] The spin coating speed of the perovskite precursor solution in the first stage (first step) was controlled at 1000 rpm, the acceleration was 1000 rpm / s, and the spin coating time was 10s. In the second stage (step 2), the spin coating speed of the perovskite precursor solution was controlled at 4000 rpm, the acceleration at 5000 rpm / s, and the spin coating time at 40 s, followed by annealing at 100℃ for 10 min to complete the preparation of the perovskite substrate.
[0075] Subsequently, a 2 mg / ml EDAI2 solution was spin-coated onto the perovskite substrate surface at a spin-coating rate of 5000 rpm for 30 seconds, followed by annealing at 100°C for 5 minutes. Then, a 2 mg / ml 4F-PEACl solution was spin-coated onto the surface at a spin-coating rate of 5000 rpm for 30 seconds, followed by annealing at 100°C for 5 minutes to complete the preparation of the perovskite passivation layer, thus obtaining the perovskite light-absorbing layer.
[0076] (5) Fabrication of electron transport layer After spin-coating the perovskite light-absorbing layer (perovskite passivation layer surface), under a vacuum degree <10 -5 Under the conditions of Pa, a fullerene layer with a thickness of 40 nm was sequentially deposited by thermal evaporation at a thermal evaporation rate of 0.5 nm / s. 60 A BCP interface modification layer with a thickness of 8 nm was added to complete the preparation of the electron transport layer modification layer (buffer layer).
[0077] A copper (Cu) electrode was thermally deposited on the electron transport layer (buffer layer) at a thermal evaporation rate of 1 nm / s, resulting in a copper (Cu) electrode deposition thickness of 100 nm. This ultimately led to the fabrication of a lead-tin hybrid perovskite solar cell, such as... Figure 1 and Figure 2 As shown.
[0078] Example 8 A method for fabricating a lead-tin hybrid perovskite solar cell based on a buried interface modification strategy includes the following steps: (1) Treatment of glass substrates with deposited ITO (hereinafter referred to as ITO glass substrates) The ITO glass substrate underwent continuous multi-step ultrasonic cleaning. In each ultrasonic cleaning tank, cleaning agent, deionized water, acetone, and ethanol were added sequentially. After ultrasonic cleaning, the ITO glass substrate was dried. The cleaned ITO glass substrate was then subjected to ultraviolet (UV) irradiation. The ITO glass substrate had a transmittance of 90%, an impedance of 15 ohms, and was purchased from a reputable supplier; model number 1.1mm 15 ohms.
[0079] (2) Preparation of hole transport layer The filtered poly(3,4-ethylenedioxythiophene)polystyrene sulfonate (PEDOT:PSS) solution was spin-coated onto the ITO substrate at 5000 rpm for 40 seconds to form a uniform film. It was then immediately transferred to a hot plate and annealed at 200°C for 30 minutes to remove residual solvent and improve film density. After the substrate cooled naturally to room temperature, it was transferred into a nitrogen glove box for subsequent experiments.
[0080] (3) Preparation of the buried interface modification layer An additive solution containing 3,4-diaminobenzenesulfonic acid (concentration of 2 mg / mL, solvent is a 1:1 volume mixture of DMF and DMSO) was spin-coated onto the hole transport layer at 3000 rpm. The layer was then placed on a hot plate and annealed at 200°C for 3 minutes to promote solvent evaporation and induce the modified layer molecules to align on the substrate surface.
[0081] (4) Preparation of perovskite light-absorbing layer Then, in the glove box, the perovskite precursor was first spin-coated onto the subsurface interface modification layer in two steps and then annealed to prepare the perovskite substrate. The perovskite material selected was FA. 0.7 MA 0.3 Pb 0.5 Sn 0.5 I 3。 Weigh out formamidinium iodide, methyl iodide, lead iodide, stannous iodide, and stannous fluoride in a molar ratio of 0.7:0.3:0.5:0.5:0.1. Dissolve the formamidinium iodide, methyl iodide, lead iodide, stannous iodide, and stannous fluoride in an organic polar solvent of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 3:1. Stir until completely dissolved, and then add 2 mg / ml of 2-amino-3-mercaptopropionate to prepare a 1.8 mol / L perovskite precursor solution.
[0082] The spin coating speed of the perovskite precursor solution in the first stage (first step) was controlled at 1000 rpm, the acceleration was 1000 rpm / s, and the spin coating time was 10s. In the second stage (step 2), the spin coating speed of the perovskite precursor solution was controlled at 4000 rpm, the acceleration at 5000 rpm / s, and the spin coating time at 40 s, followed by annealing at 100℃ for 10 min to complete the preparation of the perovskite substrate.
[0083] Subsequently, a 2 mg / ml EDAI2 solution was spin-coated onto the perovskite substrate surface at a spin-coating rate of 5000 rpm for 30 seconds, followed by annealing at 100°C for 5 minutes. Then, a 2 mg / ml 4F-PEACl solution was spin-coated onto the surface at a spin-coating rate of 5000 rpm for 30 seconds, followed by annealing at 100°C for 5 minutes to complete the preparation of the perovskite passivation layer, thus obtaining the perovskite light-absorbing layer.
[0084] (5) Fabrication of electron transport layer After spin-coating the perovskite light-absorbing layer (perovskite passivation layer surface), under a vacuum degree <10 -5 Under the conditions of Pa, a fullerene layer with a thickness of 40 nm was sequentially deposited by thermal evaporation at a thermal evaporation rate of 0.5 nm / s. 60A BCP interface modification layer with a thickness of 8 nm was added to complete the preparation of the electron transport layer modification layer (buffer layer).
[0085] A copper (Cu) electrode was thermally deposited on the electron transport layer (buffer layer) at a thermal evaporation rate of 1 nm / s, resulting in a copper (Cu) electrode deposition thickness of 100 nm. This ultimately led to the fabrication of a lead-tin hybrid perovskite solar cell, such as... Figure 1 and Figure 2 As shown.
[0086] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that no buried interface modification layer was prepared to obtain a lead-tin mixed perovskite solar cell.
[0087] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the perovskite precursor solution was not spin-coated in steps.
[0088] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the perovskite precursor solution was prepared by dissolving formamidine iodide, methyl iodide, lead iodide, stannous iodide and stannous fluoride in a polar organic solvent and stirring until completely dissolved, without adding 2-amino-3-mercaptopropionate.
[0089] Examples 1 through 8 described above can all fabricate a lead-tin hybrid perovskite solar cell based on a buried interface modification strategy. The effectiveness of lead-tin hybrid perovskite solar cells based on the buried interface modification strategy prepared in Examples 1 and 4 is now verified.
[0090] Experimental verification Microscopic tests were performed on the lead-tin mixed perovskite solar cells prepared in Example 1 and Comparative Example 1, specifically including atomic force microscopy images of the lead-tin mixed perovskite thin films of Comparative Example 1 and Example 1, as shown below. Figures 3-4 The X-ray diffraction patterns of the lead-tin mixed perovskite films of Comparative Example 1 and Example 1 are shown below. Figure 5 The electrochemical impedance spectroscopy results of the perovskite solar cells of Comparative Example 1 and Example 1 are shown in the figure below. Figure 6 The long-term stability test curves of the perovskite solar cells of Comparative Example 1 and Example 1 under a nitrogen glove box environment are shown in the figure below. Figure 7 ; Depend on Figures 3-4As can be seen, the lead-tin mixed perovskite thin film prepared in Example 1 of this invention effectively solves the common problems of interface recombination and poor crystal quality during the growth of lead-tin mixed perovskite by introducing a buried interface modification layer modified with 2,5-diaminobenzenesulfonic acid or 3,4-diaminobenzenesulfonic acid between the hole transport layer and the perovskite light-absorbing layer. Experimental data show that the buried interface exhibits excellent physical flatness, which can induce the perovskite grains above to have a regular polygonal geometric distribution, significantly improve the compactness of the film and greatly reduce the number of grain boundary defects and micropores, thereby physically blocking the leakage current path of the device.
[0091] From a structural perspective, Figure 5 The images show the X-ray diffraction (XRD) results of the lead-tin mixed perovskite films in Example 1 and Comparative Example 1 of this invention. In Example 1, the modified buried interface in the lead-tin mixed perovskite film effectively lowered the nucleation energy barrier, resulting in a perovskite film exhibiting extremely strong preferred orientations of the (100) and (200) crystal planes. The XRD diffraction peak intensity was significantly enhanced, and the full width at half maximum (FWHM) was narrowed, demonstrating the improved crystallinity and suppression of lattice defects, thus solving the problem of poor crystal quality.
[0092] From the electrochemical impedance test results of perovskite solar cells ( Figure 6 It can be seen that after the buried interface modification, the interface charge recombination resistance of the device is significantly reduced, proving that the modification strategy effectively passivates interface defects, optimizes charge transport, suppresses nonradiative recombination, greatly improves carrier extraction and transport efficiency, and solves the problems of multiple defects, severe charge recombination and energy level mismatch.
[0093] This modification strategy effectively passivates defects at the buried interface, optimizes charge transport, suppresses nonradiative recombination, and significantly improves the efficiency of carrier extraction and transport at the buried interface, solving the problems of numerous defects, severe charge recombination, and energy level mismatch.
[0094] from Figure 7 The test curves of the perovskite solar cells in Example 1 and Comparative Example 1 of this invention under a nitrogen glove box environment are shown. Figure 7As can be seen, after the buried interface modification, the device exhibits excellent long-term operational stability in an inert environment: the device in Example 1 (group 3,4-SA) maintained a photoelectric conversion efficiency of 96% of its initial value after approximately 1300 hours of aging testing in a nitrogen glove box, with minimal performance degradation; while the normalized efficiency of Comparative Example 1 under the same conditions was only 63% of its initial value, showing significant performance degradation. This proves that the modification strategy significantly improves the long-term operational stability of the device and solves the problem of poor stability. This result directly proves that the buried interface modification strategy of the present invention effectively improves the long-term operational stability of perovskite solar cells in an inert environment by passivating interface defects and optimizing the stability of the thin film structure, thus solving the problem of poor device stability in the prior art.
[0095] (0) Performance Analysis The photoelectric performance testing of perovskite solar cells includes the following steps: The current density-voltage (JV) characteristic curve of the battery was tested under an AM1.5G 100 mW / cm² simulated light source (Enlitech Solar Simulator SS-F5-3A); the measurement was performed by a computer-controlled Keithley 2400 source measurement unit in an unsealed environment within a nitrogen-filled glove box; the external quantum efficiency (EQE) was measured at room temperature, in air (40% humidity), and in an unsealed environment using a DSR100UV-B spectrometer with an SR830 lock-in amplifier and a tungsten bromide lamp as the light source.
[0096] The test results of the current density-voltage characteristic curves of the perovskite solar cells provided in Examples 1, 4 and Comparative Example 1 are shown in Table 1 below.
[0097] Table 1 As shown in Table 1, compared to Comparative Example 1, the lead-tin hybrid perovskite solar cell treated with a buried interface modification layer modified by 3,4-diaminobenzenesulfonic acid (Example 1) exhibits the best photoelectric performance, with an open-circuit voltage of 0.87V and an open-circuit voltage of 33.20mA / cm². 2 The short-circuit current density, fill factor of 80.38%, and photoelectric conversion efficiency of 23.22% were improved, and the battery treated with the buried interface modification layer modified by 2,5-diaminobenzenesulfonic acid (Example 2) also showed improved performance, with an open-circuit voltage of 0.86V and an open-circuit voltage of 33.25mA / cm². 2Compared to the device prepared without additives in Comparative Example 1, the short-circuit current density, fill factor of 79.87%, and photoelectric conversion efficiency of Example 1 are significantly improved. The photoelectric conversion efficiency of the device in Example 1 increased from 21.34% in Comparative Example 1 to 23.22%, verifying that the above-mentioned synergistic modification effect ultimately achieved a significant improvement in the photoelectric performance of the device. The data comparison between Comparative Example 2 and Example 1 verified that if step-by-step spin coating is not used and only single spin coating is used, uneven film thickness, poor coverage, and deterioration of grain morphology are likely to occur, which will aggravate carrier recombination and reduce device efficiency and stability. The photoelectric conversion efficiency of the device in Example 1 increased from 18.01% in Comparative Example 3 to 23.22%, verifying that the addition of 2-amino-3-mercaptopropionate can simultaneously achieve defect passivation and Sn suppression. 2+ Oxidation and optimization of thin film crystallization significantly improve the efficiency and stability of lead-tin perovskite devices.
[0098] This invention effectively solves the problems of poor film quality, severe interfacial recombination, and Sn in lead-tin mixed perovskite systems by introducing either 2,5-diaminobenzenesulfonic acid or 3,4-diaminobenzenesulfonic acid into the hole transport layer and the perovskite light-absorbing layer to construct a buried interface modification layer. 2+ The core bottlenecks include easy oxidation. This buried interface and the perovskite light-absorbing layer exhibit a significant synergistic effect, fundamentally repairing MA / FA cation vacancies and Sn at the film's interior and interface through strong intermolecular interactions. 2+ Oxidation defects and Sn-I antisite defects.
[0099] In terms of physical mechanism, the buried interface plays a crucial role as a growth template, precisely controlling the nucleation direction and size distribution of perovskite grains, significantly enhancing the compactness and macroscopic uniformity of the film, and eliminating pinholes and grain boundary hazards. Regarding energy level matching, the modified buried interface exhibits excellent hole extraction capability, with its work function highly compatible with the valence band of lead-tin perovskite, greatly weakening the interfacial charge transport barrier and achieving instantaneous separation of photogenerated carriers.
[0100] Furthermore, the functional groups in the additives interact with Pb in the perovskite framework. 2+ Sn 2+ The formed coordination bonds not only passivate the nonradiative recombination centers at the interface but also construct a physical barrier to inhibit the penetration of external moisture and oxygen. This comprehensive buried interface control strategy not only improves the photoelectric conversion efficiency (PCE) of solar cells to over 23% but also fundamentally enhances the thermal stability and environmental tolerance of the device, laying a solid foundation for the commercial application of lead-tin hybrid perovskites in photodetectors, LEDs, and field-effect transistors.
[0101] This invention introduces 2,5-diaminobenzenesulfonic acid or 3,4-diaminobenzenesulfonic acid as a modifier at the buried interface between the perovskite layer and the hole transport layer for in-situ modification. Employing an integrated buried interface modification strategy, it achieves synergistic modification of the hole transport layer, the buried interface, and the perovskite phase. The strongly polar sulfonic acid groups in the modifier molecules first induce the formation of directional molecular dipole moments at the interface. Through the dipole effect, the surface work function of the buried interface is effectively controlled, inducing downward bending of the perovskite interface energy band. This mechanism effectively corrects the original energy level mismatch, significantly reducing the interfacial energy level difference between the hole transport layer and the perovskite valence band, lowering the cross-interfacial transport barrier for photogenerated holes, and thus greatly improving the hole extraction and transport efficiency. Simultaneously, the nanoscale modified layer formed by the modifier at the buried interface can regulate substrate wettability and provide high-quality heterogeneous nucleation sites, guiding the precursor to preferential and uniform nucleation. During this crystallization process, the modifier molecules utilize the specifically oriented amino and sulfonic acid groups to react with Pb in the precursor. 2+ / Sn 2+ Strong coordination interactions occur. Due to the unique ortho / meta spatial configuration of 3,4-diaminobenzenesulfonic acid, it has low steric hindrance and high binding energy, effectively binding the unstable tin component. This delays and smooths out the difference in crystallization rates between lead and tin components. Under this coordination regulation mechanism, the film exhibits strong (100) and (200) preferred orientations, with regular and more consistent grain development, and a significant reduction in microscopic defects such as pinholes and cracks. Therefore, polar groups such as sulfonic acid groups in the modifier molecule can regulate the surface work function of the buried interface, optimize the interface energy level matching, reduce the interface energy level difference, lower the transport barrier of photogenerated holes, and improve the interface extraction and transport efficiency of holes.
[0102] Meanwhile, the modifier forms a uniform modified layer at the buried interface, providing high-quality heterogeneous nucleation sites, guiding the perovskite precursor to preferentially nucleate and crystallize at the interface, and effectively regulating the crystallization rate difference of lead and tin components through the coordination of amino and sulfonic acid groups with the perovskite precursor, inhibiting the excessively rapid crystallization of the Sn component, so that the film exhibits a strong (100) / (200) crystal plane preferred orientation, with more regular grains, higher density, and significantly reduced defects such as pinholes and cracks (see...). Figure 3 , Figure 4 , Figure 5 The amino and sulfonic acid groups in the modifier molecule can also interact with uncoordinated Pb on the perovskite surface. 2+ Sn 2+ It forms strong coordination bonds, passivates lead / tin vacancy defects and dangling bond defects at the buried interface and in the bulk phase, reduces the defect state density, inhibits the formation of nonradiative recombination centers, and simultaneously inhibits Sn. 2+ Oxidation and ion migration segregation prevent perovskite compositional inhomogeneity; optimized energy level matching lowers the charge transport barrier, accelerating the extraction and transport of photogenerated carriers, and combined with defect passivation, significantly reduces the charge recombination rate (see...). Figure 6 This reduces carrier recombination losses. Thanks to the synergistic effect of the above multiple mechanisms, on the one hand, the interface protection effect of the uniform and dense high-crystallinity film and the modifier jointly blocks the erosion of water vapor and oxygen, improves the device's moisture resistance and heat resistance stability, and extends its service life; on the other hand, the deep passivation of interface defects and the optimization of carrier transport dynamics enable the battery's open-circuit voltage, short-circuit current density and fill factor to be improved simultaneously, and the photoelectric conversion efficiency increased from 21.34% to 23.22% (see Table 1), taking into account the technical effects of low toxicity, high crystallinity, high stability and high efficiency.
[0103] The embodiments of the present invention have been described in detail above with reference to the accompanying drawings. However, the present invention is not limited to the above embodiments, and various changes can be made within the scope of knowledge possessed by those skilled in the art without departing from the spirit of the present invention. Furthermore, the embodiments of the present invention and the features thereof can be combined with each other unless otherwise specified.
Claims
1. A method for fabricating lead-tin hybrid perovskite solar cells based on a buried interface modification strategy, characterized in that, Includes the following steps: A hole transport solution is spin-coated onto a conductive substrate that has been treated with ultraviolet ozone, and then annealed to obtain a hole transport layer. The hole transport solution is a poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) solution. A 2,5-diaminobenzenesulfonic acid solution or a 3,4-diaminobenzenesulfonic acid solution is spin-coated onto the hole transport layer and then annealed to obtain a buried interface modification layer. The perovskite precursor solution, ethylenediamine dihydroiodide solution, and 4-fluorophenylethylamine chloride solution were sequentially spin-coated onto the buried interface modification layer and then sequentially annealed to obtain the perovskite light-absorbing layer. The perovskite precursor solution was prepared by dissolving formamidine iodide, methyl iodide, lead iodide, stannous iodide, and stannous fluoride in a polar organic solvent, stirring until completely dissolved, and then adding 2-amino-3-mercaptopropionate. An electron transport layer was prepared by spin-coating a fullerene derivative and 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline onto a perovskite light-absorbing layer using a thermal evaporation method. A lead-tin hybrid perovskite solar cell was obtained by thermally evaporating a metal electrode onto the electron transport layer.
2. The method for fabricating a lead-tin hybrid perovskite solar cell based on a buried interface modification strategy according to claim 1, characterized in that, The mass concentrations of both the 2,5-diaminobenzenesulfonic acid solution and the 3,4-diaminobenzenesulfonic acid solution were 0.1 mg / mL to 2 mg / mL. Both solutions were prepared from a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) in a volume ratio of 1:
1.
3. The method for fabricating a lead-tin hybrid perovskite solar cell based on a buried interface modification strategy according to claim 1, characterized in that, The spin coating speed for 2,5-diaminobenzenesulfonic acid solution or 3,4-diaminobenzenesulfonic acid solution is 2000 rpm to 5000 rpm, the spin coating time is 20 s to 40 s, the annealing temperature is 100 ℃ to 200 ℃, and the annealing time is 1 min to 5 min.
4. The method for fabricating a lead-tin hybrid perovskite solar cell based on a buried interface modification strategy according to claim 1, characterized in that, The mass fraction of poly(3,4-ethylenedioxythiophene)polystyrene sulfonate (PEDOT:PSS) in the solution is 1.0% to 1.5%.
5. The method for fabricating a lead-tin hybrid perovskite solar cell based on a buried interface modification strategy according to claim 1, characterized in that, The spin coating speed of the hole transport solution is 3000 rpm to 6000 rpm, the spin coating time is 20 s to 40 s, the annealing temperature is 100 ℃ to 200 ℃, and the annealing time is 10 min to 30 min.
6. The method for fabricating a lead-tin hybrid perovskite solar cell based on a buried interface modification strategy according to claim 1, characterized in that, The molar ratio of formamidinium iodide, methyl iodide, lead iodide, stannous iodide, and stannous fluoride is 0.7:0.3:0.5:0.5:0.1, and the amount of 2-amino-3-mercaptopropionate added is 0.5 mg / ml to 3 mg / ml. The concentration of the perovskite precursor solution is 0.6 mol / L to 1.8 mol / L, the concentration of the ethylenediamine dihydroiodide solution is 0.2 mg / ml to 2 mg / ml, and the concentration of the 4-fluorophenylethylamine chloride solution is 0.2 mg / ml to 2 mg / ml. The polar organic solvent is a mixture of N,N-dimethylformamide and dimethyl sulfoxide, and the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide is 3:
1.
7. The method for fabricating a lead-tin hybrid perovskite solar cell based on a buried interface modification strategy according to claim 1, characterized in that, The spin-coating and annealing steps for the perovskite precursor solution, ethylenediamine diiodide, and 4-fluorophenylethylamine chloride solution are as follows: The perovskite precursor solution was first spin-coated onto a conductive substrate with a pre-deposited hole transport layer at a speed of 1000 rpm to 2000 rpm for 10 to 15 s, and then spin-coated at a speed of 3000 rpm to 7000 rpm for 20 to 50 s for annealing. Then, ethylenediamine diiodide and 4-fluorophenylethylamine chloride solutions were spin-coated at a speed of 4000 rpm to 6000 rpm for 20 to 30 s, and then annealed. The annealing temperature for each treatment was 60℃ to 120℃, and the annealing time was 1 min to 10 min.
8. The method for fabricating a lead-tin hybrid perovskite solar cell based on a buried interface modification strategy according to claim 1, characterized in that, Fullerene derivatives are C 60 The thermally vapor-deposited metal electrode on the electron transport layer is a copper electrode, and the conductive substrate includes a substrate and a transparent electrode, wherein the transparent electrode is indium tin oxide.
9. A lead-tin hybrid perovskite solar cell based on a buried interface modification strategy, prepared by the method of fabricating a lead-tin hybrid perovskite solar cell according to any one of claims 1 to 8.
10. The application of the lead-tin hybrid perovskite solar cell based on the buried interface modification strategy according to claim 9 in optoelectronic devices.